Pemikiran Pendidikan Islam KH. Hasyim Asyâ€™ari (Perspektif Epistimologi Sosial Keagamaan Dan Konsep Pendidikan Islam Bagi Guru Dan Peserta Didik) - Martono, Martono (Al-Fikr: Jurnal Pendidikan Islam, 2020)
Kyai Hasyim is known as a figure who is hungry for religious knowledge (Islam). To treat his thirst, KyaiHasyim traveled various famous places in Java at that time. Not only that, the cleric Hasyim also spent a longtime to explore Islam in the holy land (Mecca and Medina). It can be given, Kyai Hasyim is among the santriwho are really serious about Javanese philosophy, â€œluru ilmu kanti lelakuâ€ (seeking knowledge bywandering) or wandering students.